Fuzzy Probabilistic Analysis of Steel Structure Focused on Reliability Design Concept of Eurocodes - Kala, Z. (Nonlinear Analysis: Modelling and Control, 2007)
The modern unification of the European standards EUROCODE requires securing a constant quality of metallurgical production in the EU countries. In this paper, experimentally found statistical characteristics of yield stress, ultimate tensile strength and ductility of Czech and Austrian steel are presented. In the probabilistic reliability analysis, the experimentally found yield stress histograms of structural steel S235 of both Czech and Austrian manufacturing processes are considered as basic parameters. The reliability of steel members designed according to EUROCODE 3 is investigated. The objective of the studies is the verification of partial safety factors of load-carrying capacity, and of load action given in the standard EN1990. Differences in failure probabilities of steel members of Czech and Austrian production are studied in connection with the influence of model fuzzy uncertainties in the determination of load action and load-carrying capacity values.
Keywords: Eurocode; stability; constructional steel; stochastic yield stress; structural reliability; fuzzy sets; fuzzy reliability